2016
DOI: 10.1186/s12931-016-0414-8
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular autonomic alterations in hospitalized patients with community-acquired pneumonia

Abstract: BackgroundAlterations of cardiac autonomic control (CAC) are associated with poor outcomes in patients with infectious and non-infectious diseases. No evaluation of CAC in patients with community-acquired pneumonia (CAP) has been performed so far. The aim of the study was to assess CAC in patients with CAP and evaluate the impact of its alterations on disease severity and clinical outcomes in a multicenter, prospective, observational study.MethodsConsecutive patients hospitalized for CAP were enrolled between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
1
11
1
Order By: Relevance
“…A similar autonomic profile represents a stiff system, which is less capable to adequately respond to external and internal stressors stimuli. In other acute clinical conditions, like community-acquired pneumonia [34], it has been shown that such an autonomic profile is associated with worse clinical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A similar autonomic profile represents a stiff system, which is less capable to adequately respond to external and internal stressors stimuli. In other acute clinical conditions, like community-acquired pneumonia [34], it has been shown that such an autonomic profile is associated with worse clinical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with cardiac autonomic dysfunction present several associated lung diseases, such as chronic obstructive pulmonary disease (COPD) [6,7], pulmonary arterial hypertension (PAH) [17], and cystic fibrosis (CF) [18] compared to age-matched controls. Although global HRV is reduced in patients with several lung diseases compared to healthy controls, the sympatho-vagal balance may be different considering disease severity and respiratory function [5,6]. The results of the current Figure 3.…”
Section: Discussionmentioning
confidence: 75%
“…Although there is no direct relation with the degree of airway narrowing in cardiac autonomic modulation, chronic hypoxemia can increase cardiac vagal activity and depress the sympathetic modulation of COPD patients [7]. Recently, a similar cardiac autonomic profile was reported in patients with community-acquired pneumonia (CAP) [5]. The global contribution from cardiac autonomic control, represented by the total power index of HRV spectral analysis, was reduced in CAP patients in comparison with healthy controls.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations